Requesting with an appropriate degree: The request speech act competence of BIPA learners - Kurniawati, Wira; Ginting, Silvia Rehulina (Universitas Ahmad Dahlan, 2026)
BIPA learners not only need to understand the structure of the Indonesian language they are learning, but also its functional aspects in accordance with the situation and context of use. This study aims to analyze the request speech act competence of BIPA learners from the perspective of second language pragmatic acquisition. Based on a sociopragmatic perspective, utilizing the variables of Distance, Power, and Rank of Imposition proposed by Brown & Levinson, eight speech situations were constructed as instruments for data collection. Through a written discourse completion test, 17 upper-intermediate BIPA learners from Taiwan participated as respondents in this study. The data analysis employed the framework of request speech act realization as summarized by Schauer. The findings indicate that the BIPA learners have developed their pragmatic competence in producing request speech acts, although they still face difficulties in adjusting levels of politeness and situational context. Based on the realization of speech acts in terms of core and peripheral elements, the utterances produced tend to be overly long and excessively polite. This tendency is influenced by instructional emphasis on formal language, as well as differences in the pronominal system between Indonesian and Mandarin as their first language. The challenges identified are related to developing pragmatic competence, the influence of first-language cultural norms, and limited experience with real-life contexts. Thus, these upper-intermediate BIPA learners are at a transitional stage and are not yet fully flexible in adapting to contextual demands. The implications of this study highlight the importance of context-based BIPA instruction and the need for more explicit integration of pragmatic aspects in second language learning.